2022
DOI: 10.1002/ejoc.202201043
|View full text |Cite
|
Sign up to set email alerts
|

Aza‐oxyallyl Cations and Their Applications in (3+m) Cycloaddition Reactions

Abstract: Aza‐oxyallyl cations, as proposed by Sheehan in the 1960s have garnered significant attention among the synthetic organic community, owing to their diverse reactivity profile for constructing N‐scaffolds of biological interest. During its initial growth, aza‐oxyallyl cations were used effectively as a 3‐unit synthon as 1,3 dipoles to create N‐heterocycles via cycloaddition reactions, wherein aza‐oxyallyl cation served as electrophilic counterpart. Recently, new variations of aza‐oxyallyl cations reactivity hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 105 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…These findings demonstrated that the electron-donating groups –OBn or other –OR groups could remarkably improve the reaction efficiency. 20 Considering the higher reactivity of non-substituted α-bromohydroxamates than that of α-substituted α-bromohydroxamates and previous reports, 13,15 a a plausible mechanism of the reaction process is proposed in Scheme 1. α-Halohydroxamate was reacted with NaI to yield the corresponding iodide.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings demonstrated that the electron-donating groups –OBn or other –OR groups could remarkably improve the reaction efficiency. 20 Considering the higher reactivity of non-substituted α-bromohydroxamates than that of α-substituted α-bromohydroxamates and previous reports, 13,15 a a plausible mechanism of the reaction process is proposed in Scheme 1. α-Halohydroxamate was reacted with NaI to yield the corresponding iodide.…”
Section: Resultsmentioning
confidence: 97%
“…In recent years, α-halohydroxamates have been extensively used as novel building blocks to construct various important N-heterocycles. 13 So far, the application of α-halohydroxamates in a range of [3 + 1], 14 [3 + 2], 15 [3 + 3], 16 and [3 + 4] 17 domino and/or cycloaddition reactions has been well explored with the generation of a variety of four- to seven-membered aza-heterocyclic rings. Specifically, these unique synthons are easily accessible from the corresponding amines.…”
Section: Introductionmentioning
confidence: 99%
“…The IN route has been similarly studied for the delivery of nucleotide-based drugs. The importance of oligonucleotide therapy in the treatment of chronic inflammatory respiratory diseases is comprehensively discussed in a review published by Mehta et al where they also emphasised the importance of delivery routes including nasal administration [198]. Many investigations have employed the olfactory pathway to transport oligonucleotides or oligonucleotide-loaded nanoparticles [199][200][201][202][203][204][205][206][207] to the brain.…”
Section: In Delivery Of Biologics To the Cnsmentioning
confidence: 99%
“…Dipolar cycloadditions of the crucial C(CO)N synthon’s synthetic equivalents have therefore attracted considerable interest. While the reactivity of α-haloamides has been widely documented, only two enantioselective dipolar cycloadditions have been reported and rely on the activation of the electrophilic cycloaddition partner by a squaramide organocatalyst . The group of Hamada exploited the dipolar properties of acrylamides to design an enantioselective (3 + 2) cycloaddition based on a chiral iminium activation method .…”
Section: Introductionmentioning
confidence: 99%